Tamoxifen for prevention of breast cancer: extended long-term follow-up of the IBIS-I breast cancer prevention trial. Issue 1 (January 2015) - Cuzick, Jack; Sestak, Ivana; Cawthorn, Simon; Hamed, Hisham; Holli, Kaija; Howell, Anthony; Forbes, John F; on behalf of the IBIS-I Investigators, †
Summary Background Four previously published randomised clinical trials have shown that tamoxifen can reduce the risk of breast cancer in healthy women at increased risk of breast cancer in the first 10 years of follow-up. We report the long-term follow-up of the IBIS-I trial, in which the participants and investigators remain largely masked to treatment allocation. Methods In the IBIS-I randomised controlled trial, premenopausal and postmenopausal women 35–70 years of age deemed to be at an increased risk of developing breast cancer were randomly assigned (1:1) to receive oral tamoxifen 20 mg daily or matching placebo for 5 years. Patients were randomly assigned to the two treatment groups by telephone or fax according to a block randomisation schedule (permuted block sizes of six or ten). Patients and investigators were masked to treatment assignment by use of central randomisation and coded drug supply. The primary endpoint was the occurrence of breast cancer (invasive breast cancer and ductal carcinoma in situ), analysed by intention to treat. Cox proportional hazard models were used to assess breast cancer occurrence and mortality. The trial is closed to recruitment and active treatment is completed, but long-term follow-up is ongoing. This trial is registered with controlledtrials.com, number ISRCTN91879928. Findings Between April 14, 1992, and March 30, 2001, 7154 eligible women recruited from genetics clinics and breast care clinics in eight countries were enrolled into the IBIS-I trial and were randomly allocated to the two treatment groups: 3579 to tamoxifen and 3575 to placebo. After a median follow up of 16·0 years (IQR 14·1–17·6), 601 breast cancers have been reported (251 [7·0%] in 3579 patients in the tamoxifen group vs 350 [9·8%] in 3575 women in the placebo group; hazard ratio [HR] 0·71 [95% CI 0·60–0·83], p<0·0001). The risk of developing breast cancer was similar between years 0–10 (226 [6·3%] in 3575 women in the placebo group vs 163 [4·6%] in 3579 women in the tamoxifen group; hazard ratio [HR] 0·72 [95% CI 0·59–0·88], p=0·001) and after 10 years (124 [3·8%] in 3295 women vs 88 [2·6%] in 3343, respectively; HR 0·69 [0·53–0·91], p=0·009). The greatest reduction in risk was seen in invasive oestrogen receptor-positive breast cancer (HR 0·66 [95% CI 0·54–0·81], p<0·0001) and ductal carcinoma in situ (0·65 [0·43–1·00], p=0·05), but no effect was noted for invasive oestrogen receptor-negative breast cancer (HR 1·05 [95% CI 0·71–1·57], p=0·8). Interpretation These results show that tamoxifen offers a very long period of protection after treatment cessation, and thus substantially improves the benefit-to-harm ratio of the drug for breast cancer prevention. Funding Cancer Research UK (UK) and the National Health and Medical Research Council (Australia).